(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper focuses on addressing the persistent financial challenges in Nigeria’s education sector, particularly in secondary and higher education institutions. It examines the specific issues that hinder the development of the educational system, emphasizing how financial inefficiencies negatively impact the quality of education. The study highlights the dangers posed by a poorly managed financial system and identifies pathways and strategies for effective educational financing. Various perspectives on improving financial management within the education sector are explored to provide a holistic approach to reform. The paper offers several key recommendations to enhance financial accountability and resource utilization in the sector. It advocates for the proper training of educational administrators on public fund management, which can be achieved through well-structured conferences and workshops. Furthermore, school inspectors should be mandated to report uncompleted or abandoned projects to the appropriate authorities for corrective action. The selection of vice chancellors in higher institutions should prioritize not only academic excellence and indigenization but also demonstrated managerial competence. These measures aim to strengthen governance, accountability, and sustainable development in Nigeria’s education system.